Antioxidant capacity, anti-inflammatory activity, and mutagenicity of Sterculia lychnophora (Pangdahai) polysaccharide - Ping-Hsiu Huang; Chien-Shan Chiu; Wen-Chien Lu; Chang-Wei Hsieh; Zeng-Chin Liang; Li-Ling Fan; Chiun-Chung R. Wang; Po-Hsien Li (Arabian Journal of Chemistry, 2024)
Dried boat-fruited ripped seeds of Sterculia lychnophora, commonly known as Pangdahai, are frequently used in traditional Chinese medicines and functional foods. However, research on these constituents is limited. In this study, the extraction of Pangdahai polysaccharide (PP) was investigated using different solvents (deionized water, 50 % methanol, and 50 % ethanol), and its chemical composition, antioxidant capacity, and anti-inflammatory activity were analyzed. Additionally, the Ames test was used to evaluate PPs’ food safety and mutagenicity. The results showed that the yields of PPs extracted with the three solvents ranged from ∼ 19 % to 21 % and that their monosaccharide compositions (rhamnose, arabinose, galactose, and glucose) were similar, with slightly different proportions. Moreover, the antioxidant capacity of all three PPs showed concentration-dependent effects. The EC50 values for each antioxidant were approximately 0.71–1.35 mg/mL for 1, 1-diphenyl-2-picrylhydrazyl free radical scavenging ability, 1.88–46.13 µg/mL for 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging ability, 2.22–3.61 mg/mL for ferric reducing antioxidant power, and 0.52–3.11 mg/mL for hydroxyl radical scavenging ability. At concentrations below 500 µg/mL, the anti-inflammator activity of PPs promoted cell proliferation while inhibiting nitric oxide production at concentrations ranging from 31.25 to 125 µg/mL. In the Ames test, PPs (1–5 mg/plate) exhibited no toxicity or mutagenicity against the five strains of Salmonella typhimurium (TA98, TA100, TA102, TA1535, and TA1537). These findings will particularly be of interest to individuals involved in PP-related research or commercial enterprises. Thus, the findings of this study will elucidate the bioactive components and potential benefits of PP, making it especially valuable to researchers and practitioners in the Pangdahai industry and expanding opportunities for industrial development.